Demographic features and antibiotic resistance among children hospitalized for urinary tract infection in northwest Iran - Ghorashi Z (Infection and Drug Resistance, 2011)
Ziaaedin Ghorashi1, Sona Ghorashi2, Hassan Soltani-Ahari1, Nariman Nezami3 1Department of Pediatrics, Tabriz University of Medical Sciences, 2Young Researchers Club, Tabriz Branch, Tabriz Islamic Azad University, 3Drug Applied Research Center, Tabriz University of Medical Sciences, Tabriz, Iran Introduction: Urinary tract infection (UTI) is the most common serious bacterial infection during infancy. The aim of the present study was to evaluate demographic characteristics, clinical presentations and findings, and antimicrobial resistance among infants and children hospitalized in Tabriz Children's Hospital, Tabriz, Iran. Methods: In this descriptive observational study, 100 children who had been admitted with UTI diagnosis to Tabriz Children's Hospital from March 2003 to March 2008 were studied. Demographic characteristics, chief complaints, clinical presentations and findings, urine analysis and cultures, antimicrobial resistance, and sonographic and voiding cystourethrographic reports were evaluated. Results: The mean age of patients was 35.77 ± 39.86 months. The male to female ratio was 0.26. The mean white blood cell count was 12,900 ± 5226/mm3. Sixty-two percent of patients had leukocytosis. The most common isolated pathogen was Escherichia coli spp (77%) followed by Klebsiella spp (10%), Enterobacter spp (9%), and Enterococcus spp (4%). Isolated pathogens were highly resistant to ampicillin, cotrimoxazole, and cephalexin (71%–96%), intermediate sensitivity to third-generation cephalosporins, and highly sensitive to ciprofloxacin (84.4%), amikacin (83.8%), and nitrofurantoin (82.8%). Conclusion: The most common pathogen of UTI in the hospitalized children was E. coli spp. The isolated pathogens were extremely resistant to ampicillin, and highly sensitive to ciprofloxacin and amikacin. Keywords: urinary tract infection, antibiotic, resistance, sensitivity, Escherichia coli